PENGEMBANGAN SUMBER DAYA MANUSIA BERBASIS KOMPETENSI - Ni Made Gunastri (STIMI Handayani Denpasar, 2013)
The success of an organization is determined by the quality of thosepeople who work in it. Competency is a developing problem, in which it hasbeen frequently discussed in the middle of society nowadays, especially when anorganization is facing challenges and competitions that are getting harder andharder. Due to those competition matters as the impacts of quick changes in bothtechnology and environment on each aspects of the human life, a manager has nomore choice, except to make the organization that he or she is leading now, to be notonly able to give a consumer satisfaction, produce any high quality and competitiveproducts in the market, and has an orientation on its customer value. As the result,the organization will not only be oriented to achieve a high productivity of work, butalso it will also deal with the performance on its process. The employees’ competence supports the success of an organization so much andit is obviously able to make its mission come true by paying attention to the relationbetween both selection and selection plan. Therefore, the role of competency inan organization will be apparently not only able to enhance the high productivityof an organization without accompanied by the rewarding system and measuredperformance evaluation.